Analysis of dietary fats intake and lipid profile in Chilean patients with glucose transport type 1 deficiency syndrome: similarities and differences with the reviewed literature - Salazar, María Florencia; Leal-Witt, María Jesús; Parga, Valentina; Arias, Carolina; Cornejo, Verónica (Frontiers in Nutrition, 2024)
Introduction: Glucose transporter type 1 deficiency syndrome (GLUT1-DS) is a neurological disorder caused by mutations in the SLC2A1 gene. The main treatment is ketogenic diet therapy (KDT), which changes the brain's energy substrate from glucose to ketone bodies. The diet controls seizures, but there may be side effects such as dyslipidemia. This study aimed to describe the type of fats ingested by the Chilean cohort of patients with GLUT1-DS and analyze for alterations in the lipid profile. Methods: A GLUT1-DS group and a control group were formed, each with 13 subjects who were matched by age, gender, and nutritional status. Anthropometry, dietary intake, including types of fat, and blood tests were evaluated (lipid and liver profile, and 25-hydroxyvitamin D levels). Results: A high-fat diet, especially saturated fat, was identified in the GLUT1-DS group (38% of total calories), with the use of medium-chain triglycerides (17% of total calories). In addition, GLUT1-DS participants had a higher intake of monounsaturated (MUFA) and polyunsaturated (PUFA) fats and adequate consumption of omega-3 (2% of total calories). Despite the GLUT1-DS group receiving on average 80% of its total energy as fats, it is important to highlight that 50% are MUFA+PUFA fats, there were no significant differences in the lipid and liver profile compared to the control group. Conclusion: KDT did not negatively impact lipid profile, despite a high intake of fats. It is important to monitor lipid profiles, in a personalized and constant manner, to prevent future nutritional risks.